2017
DOI: 10.18488/journal.8/2017.5.1/8.1.98.109
|View full text |Cite
|
Sign up to set email alerts
|

Households Preferences and Willingness to Pay for Watershed Services Attributes in North Selangor Peat Swamp Forest Malaysia

Abstract: Realising the objective of payment for ecological services (PES) Contribution/ OriginalityThis study contributes to the existing literature by using the choice experiment approach to analyze willingness to pay for forest watershed conservation. It is also one of very few studies which have investigated Households' Preferences and Willingness to Pay for Watershed Services attributes in the forest reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(18 reference statements)
1
1
0
1
Order By: Relevance
“…However, the slope of this increase has a decreasing trend which shows that water is a tensionless good for the farmers in the basin because by increasing water price, its demand decreases. These findings are similar to those of Abdulkarim et al (2016) who looked at the paying of farmers for water irrigation in North West Selangor, Malaysia, and the results of Amponin et al (2007) who investigated the domestic water users' WTP for watershed protection in Tuguegarao City, the Philippines. The results of both studies showed that people have a high amount of WTP, which contradicts the results of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…However, the slope of this increase has a decreasing trend which shows that water is a tensionless good for the farmers in the basin because by increasing water price, its demand decreases. These findings are similar to those of Abdulkarim et al (2016) who looked at the paying of farmers for water irrigation in North West Selangor, Malaysia, and the results of Amponin et al (2007) who investigated the domestic water users' WTP for watershed protection in Tuguegarao City, the Philippines. The results of both studies showed that people have a high amount of WTP, which contradicts the results of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Lebih lanjut dijelaskan bahwa rumah tangga yang memiliki lahan pertanian kecil memiliki kesempatan untuk memperoleh pendapatan pertanian lebih sedikit sehingga kurang bersedia membayar. Sedangkan masyarakat yang memiliki lahan pertanian yang lebih besar mempu menghasilkan nilai pertanian lebih besar sehingga kesediaan membayarnya akan lebih tinggi (Abdulkarim et al, 2016;Ndetewio et al, 2013).…”
Section: Faktorunclassified
“…Figure 1. Location of study area with rainfall gauging station (Source: Abdulkarim et al, 2017) Statistical relationship was established between the flow data from HEC-HMS and recorded flow data from gaging station ID 2918401. Both hourly and daily flow and rainfall data covering 2013 to 2015 were obtained from Malaysian Department of Irrigation and Drainages (DID) and used in the runoff estimation.…”
Section: Runoff Estimation Using Recorded Streamflow Data and Hec-hmsmentioning
confidence: 99%